2008
DOI: 10.3168/jds.2007-0530
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Feeding Behavior as Possible Indicators for the Automatic Monitoring of Health Disorders in Dairy Cows

Abstract: Changes in short-term feeding behavior of dairy cows that occur with the onset of the health disorders ketosis, acute locomotory problems, and chronic lameness were investigated using data collected during previous experiments. The objective of the study was to describe and quantify those changes and to test their suitability as early indicators of disease. Feed intake, feeding time, and number of daily feeder visits were recorded with computerized feeders. Ketosis in 8 cows was characterized by rapid daily de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
218
11
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(250 citation statements)
references
References 33 publications
14
218
11
7
Order By: Relevance
“…The plasma BHBA concentration reached was 1.7 ± 0.1 mmol/L, which was clearly above the considered concentration of 1.2 to 1.4 mmol/L referring to subclinical ketosis (Duffield et al, 2009;Ospina et al, 2010). The expected reduction of DMI in HyperB cows, as shown in cows with spontaneously elevated ketone body concentrations (Bareille et al, 2003;González et al, 2008), was not observed in our study. Subcutaneous injection of BHBA (10 mmol/kg of BW) in rats (Moor et al, 1976;Langhans et al, 1983), intraperitoneal BHBA infusion (15 mmol/kg 0.75 ) in pigmy goats (Rossi et al, 2000), and intracerebroventricular BHBA infusion (18mM/d) in dairy cows (Kuhla et al, 2011) decreased feed intake.…”
Section: Discussioncontrasting
confidence: 42%
“…The plasma BHBA concentration reached was 1.7 ± 0.1 mmol/L, which was clearly above the considered concentration of 1.2 to 1.4 mmol/L referring to subclinical ketosis (Duffield et al, 2009;Ospina et al, 2010). The expected reduction of DMI in HyperB cows, as shown in cows with spontaneously elevated ketone body concentrations (Bareille et al, 2003;González et al, 2008), was not observed in our study. Subcutaneous injection of BHBA (10 mmol/kg of BW) in rats (Moor et al, 1976;Langhans et al, 1983), intraperitoneal BHBA infusion (15 mmol/kg 0.75 ) in pigmy goats (Rossi et al, 2000), and intracerebroventricular BHBA infusion (18mM/d) in dairy cows (Kuhla et al, 2011) decreased feed intake.…”
Section: Discussioncontrasting
confidence: 42%
“…Investigators have used algorithms with 7 day rolling average feeding times as baselines to identify behavioral changes correlated with painful locomotive conditions in dairy cows days before farm staff were able to diagnose lameness. 63 Monitoring animal feeding behavior and intake can provide insight into potential changes in wellness or pain status. Setup, maintenance, training, and expense are all potential disadvantages that must be considered when evaluating remote feed intake and behavior systems.…”
Section: Feed Intake and Behavioral Monitoringmentioning
confidence: 99%
“…In addition, using data from automated feed stations, lameness has been found to decrease feeding time (Gonzàlez et al, 2008). Thus, the behavioural time-budget of a dairy cow changes during lameness, making changes in several aspects of activity possible indicators of lameness.…”
Section: Introductionmentioning
confidence: 99%